Pre-equilibrium emission in nuclear reactions : fundamentals, measurements and analysis /: fundamentals, measurements and analysis. (2021) - (Professor of physics), Singh, B. P; Sharma, Manoj K; (Emeritus Professor of Physics), Prasad, R
No abstract available